2023
DOI: 10.1007/s00122-023-04313-1
|View full text |Cite|
|
Sign up to set email alerts
|

Stress memory and its regulation in plants experiencing recurrent drought conditions

Abstract: Developing stress-tolerant plants continues to be the goal of breeders due to their realized yields and stability. Plant responses to drought have been studied in many different plant species, but the occurrence of stress memory as well as the potential mechanisms for memory regulation is not yet well described. It has been observed that plants hold on to past events in a way that adjusts their response to new challenges without altering their genetic constitution. This ability could enable training of plants … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 142 publications
0
9
0
Order By: Relevance
“…Heat stress activates various signal transduction pathways to induce cellular responses to high temperature, including the acquisition of heat stress tolerance and the establishment of heat stress memory ( Yamaguchi, 2021a ; Yamaguchi, 2021b ; Ramakrishnan et al., 2022 ; Sharma et al., 2022 ; Charng et al., 2023 ; Kambona et al., 2023 ). Although many studies have shed light on these physiological responses in terrestrial plants, our knowledge about tolerance to and memory of heat stress in algae is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat stress activates various signal transduction pathways to induce cellular responses to high temperature, including the acquisition of heat stress tolerance and the establishment of heat stress memory ( Yamaguchi, 2021a ; Yamaguchi, 2021b ; Ramakrishnan et al., 2022 ; Sharma et al., 2022 ; Charng et al., 2023 ; Kambona et al., 2023 ). Although many studies have shed light on these physiological responses in terrestrial plants, our knowledge about tolerance to and memory of heat stress in algae is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Acclimation to changes in environmental conditions is crucial for the survival of plants, as plants cannot move away from abiotic and biotic stresses. Recent studies have demonstrated that plants “memorize” the experience of exposure to non-lethal environmental changes, allowing them to acquire tolerance to subsequent exposure to environmental changes that would normally be lethal ( Sharma et al., 2022 ; Kambona et al., 2023 ). Indeed, plants withstand extremely high temperatures, which are lethal to plants in the native state, following growth at optimal temperatures for several days after exposure to non-lethal high temperatures ( Yamaguchi, 2021a ; Yamaguchi et al., 2021b ; Ramakrishnan et al., 2022 ; Charng et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that sustained ABA accumulation may aid the recovery processes by facilitation of embolism repair by decreasing stomatal conductance and water loss, which favors embolism refilling processes [41,42]. Also, memory effects due to ABA increase during the first stress encounter can increase the tolerance to subsequent stresses and yield [43]. The negative…”
Section: Trade-offs Of Aba Effects On Plant Performancementioning
confidence: 99%
“…Adaptation to such stresses is crucial for optimizing performance of plants and stability of their successive generations. Developing stress-tolerant plants remains the ultimate goal of plant breeders due to their superior yields and stability ( Kambona et al., 2023 ). Genetic manipulation of plants remains the most prominent approach to alleviating poverty, due to its potential to increasing crop yield and mitigating nutrient deficiencies, enabling the cultivation of salt affected lands, overcoming energy crisis and production of cost-efficient biopharmaceuticals using plants as cellular factories ( Ahmad and Mukhtar, 2017 ).…”
Section: Introductionmentioning
confidence: 99%